# maths

posted by .

express x-1/(x+1)(x-2)^2 into partial fractions

• maths -

let
(x-1)/((x+1)(x-2)^2) = A/(x-1) + B/(x-2) + C/(x-2)^2

multiply both sides by (x+1)(x-2)^2

A(x-2)^2 + B(x-2)(x+1) + C(x+1) = x-1

let x = 2, ---> 3C = 1 or C=13
let x = -1 ---> 9A + -2 or A = -2/9
let x = 0 ----> 4A - 2B + C = -1
4(-2/9) - 2B + 1/3 = -1
times 9
-8 - 18B + 3 = -9
B = 2/9

so (x-1)/(x-2)^2 = -2/(9(x+1)) + 2/(9(x-2)) + 1/(3(x-2)^2)

verified with Wolfram:
http://www.wolframalpha.com/input/?i=%28x-1%29%2F%28%28x%2B1%29%28x-2%29%5E2%29

• typo - maths -

in the middle of the solution above the line should read:

et x = 2, ---> 3C = 1 or C=1/3

## Similar Questions

2. ### Binomial

Help me on this one :( Express y= (7-3x-x^2)/[((1-x)^2)(2+x)] in partial fractions. Hence, prove that if x^3 and higher powers of x may be neglected, then y=(1/8)(28+30x+41x^2) I did the first part of expressing it in partial fractions. …
3. ### maths

Resolve 3x/x^2-x-12 into partial fractions
4. ### Math- Partial Fractions

Decompose the following into partial fractions after factoring the denominator as much as possible. Please show some work so I can understand how you did it. 1)x^2/((x-1)(x^2+5x+4)) 2)(3x^3-5x^2+12x+4)/(x^4-16) 3)1/(x^2 (x+1)^2 ) 4)(x+1)/((x^2+1) …
5. ### math

Express (5x+2)/(2x-1)(x+1) into partial fractions and hence expand the expression as a series in ascending power of x giving the first 4 terms
6. ### math/algebra

Express x^2 - 3x/x^2 - 1 As partial fractions
7. ### Math

Express 13-15x^2/(x^2-1)(x 3) into partial fractions
8. ### maths -partial fractions

Resolve in partial form (x^2+15)/(x+3)^2(x^2+3)
9. ### Math

Express 2x^3-9/x^3+6x^2+8x as partial fractions
10. ### Alex

Express x^3-4/x^2(x+2) into partial fractions

More Similar Questions

Post a New Question